Regenerative therapies for refractory thin endometrium in in vitro fertilization - Chen, Hsuan-Ju; Chen, Ming-Jer; Chang, Po-Han; Lu, Yu-Ting; Hsueh, Ya-Wen; Chang, Chia-Wei; Hsu, Hsi-Chen; Yang, Tung-Chuan; Lin, Wu-Chou; Lee, Maw-Sheng; Chang, Hsun-Ming (Frontiers in Cell and Developmental Biology, 2025)
Refractory thin endometrium remains a significant challenge in assisted reproductive technology, frequently leading to poor endometrial receptivity and suboptimal outcomes in in vitro fertilization (IVF) cycles. In recent years, regenerative therapies such as platelet-rich plasma (PRP), granulocyte colony-stimulating factor (G-CSF), growth hormone (GH), and stem cell-based interventions, have gained increasing attention as promising strategies to enhance endometrial function and receptivity. Notably, growing interest has also focused on the therapeutic potential of stem cell-derived exosomes in facilitating endometrial repair, although clinical evidence remains limited. Recent studies suggest that regenerative interventions are administered either locally, via intrauterine infusion or sub-endometrial injection, or systemically at various stages of the IVF protocol. Among these approaches, PRP and G-CSF have shown consistent benefits in increasing endometrial thickness and improving clinical pregnancy rates, particularly in frozen embryo transfer cycles. GH has been associated with enhanced endometrial proliferation, while stem cell-based therapies, particularly those utilizing mesenchymal or bone marrow-derived stem cells, demonstrate potential to restore severely damaged endometrial tissue. In preclinical models, stem cell-derived exosomes have been shown to promote endometrial regeneration and angiogenesis, underscoring their potential for future clinical application. Despite these encouraging developments, most studies are constrained by small sample sizes, methodological heterogeneity, and variable treatment protocols, which hinder the ability to draw definitive conclusions. Taken together, regenerative therapies represent a promising new direction in managing refractory thin endometrium among IVF patients. Preliminary clinical outcomes, particularly those associated with PRP, G-CSF, GH, and stem cell-based approaches, are encouraging. However, robust, large-scale, and well-controlled clinical trials are crucial for validating efficacy, optimizing therapeutic protocols, and ensuring long-term safety. Among these innovations, stem cell-derived exosomes stand out as an especially exciting and emerging frontier in reproductive medicine, supported by compelling preclinical evidence that merits further investigation.